Nonlinear Buckling Analysis and Optimization Design of the Y-Type Composite Insulator String - Hua Bao; Lingzhi Xia; Shengcong Chai; Yang Cheng; Songyuan Cao; Zhiwen Lan (Advances in Civil Engineering)
Under the action of extreme wind load, the overhead transmission line will lead to the fracture of the traditional V-type insulator string, which greatly affects the safety of the power system. Compared with the V-type insulator string, the Y-type insulator string has better stability under the wind load. Therefore, the overhead lines in the mountainous areas of Anhui Province are taken as the research object, considering the combined effect of wind load and conductor dead weight, and through theoretical derivation, the calculation formula of insulator string wind deflection angle is obtained. Using numerical simulation software, the nonlinear mechanical analysis of Y-type insulator strings is conducted, and under the action of different wind speeds, the windage yaw angle and unloading angle of the Y-type insulator string are obtained. Compared with the calculation results of the V-type insulator string, the stability of the Y-type insulator string in the structure is better than that of the V-type insulator string, and the Y-type insulator string can make full use of the distance between layers and the gap margin of the tower head, reduce the length of the cross arm, and reduce the weight of the tower, which has obvious advantages. Combined with the results of theoretical analysis and numerical simulation, the optimal design method of the Y-type insulator string is given. Under the condition of ensuring the safety and stability of insulators, the distance of the cross arm is shortened as much as possible and the weight of the transmission line tower is reduced. The research results will provide a theoretical reference for engineering design and improvement.